The Effect of E-Service Quality on E-Loyalty Mediated by E-Satisfaction and E-Trust on the Transjatim-Ajaib E-Ticket Application Using the SEM-PLS Approach - Rizki Amalia Utami; Ery Tri Djatmika Rudijanto Wahyu Wardhana; Agus Hermawan (Indonesian Journal of Islamic Economics and Finance, 2026)
The development of digital technology encourages transportation service providers to improve the quality of service through the implementation of an electronic system, the Transjatim-Ajaib e-ticket application. This study aims to analyze the influence of e-service quality on e-loyalty with e-satisfaction and e-trust as mediation variables. The research uses a quantitative approach with purposive sampling techniques in data collection. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) using the SmartPLS 4.0 application. The results of the study show that e-service quality has a positive and significant effect on e-loyalty, e-satisfaction, and e-trust. Furthermore, e-satisfaction and e-trust have been proven to have a positive and significant effect on e-loyalty. Indirect effect testing showed that e-trust and e-satisfaction were able to mediate the influence of e-service quality on e-loyalty significantly. However, the role of e-satisfaction mediation is relatively smaller than that of e-trust. These findings indicate that improving the quality of electronic services, especially in the aspects of ease of use, system reliability, transaction security, and information accuracy, can strengthen user trust and satisfaction thereby encouraging the formation of customer loyalty to the TransJatim-Ajaib e-ticket application.